Charting the future of PLOS Medicine: Priorities for evidence, impact, and equity. - Helen Lumbard; Till Baernighausen (PLoS Medicine)
As PLOS Medicine enters a new chapter, its leadership sets out a bold editorial vision grounded in evidence, impact and equity. In a rapidly evolving global health landscape, the journal reaffirms its commitment to diversity, openness, and actionable science, ensuring research not only reflects the world's needs, but drives meaningful change.